THE EFFECT OF PEGAGAN GEL (CENTELLA ASIATICA (L.) URBAN) ON WOUND HEALING PROCESSES IN MICE (MUS MUSCULUS) IN VIVO - Hendri Poernomo; Setiawan DS (ODONTO : Dental Journal, 2022)
Background : Tooth extraction and incision are procedures that are often performed in dentistry that cause injury and damage to oral tissues. Injuries to the oral tissue must be treated immediately so as not to interfere with the stomatognathic system. Pegagan (Centella asiatica (L.) Urban) is one of the medicinal plants used to accelerate wound healing. The purpose of the study was to determine the effect of giving extract pegagan gel on the oral mucosal wounds of mice (Mus musculus) in various concentrations on the number of fibroblast cells.Methods : The research method used experimental post test only control group design. Data analysis used One Way Anova test and Least Significant Difference (LSD) test. The experimental used were 24 male mice aged 6-8 weeks weighing 20-25 grams and healthy, divided into 4 (four) groups. The extraction wounds were smeared with 5%, 10%,15% concentration of pegagan extract gel and the placebo was smeared for 1 minute and done twice a day. Experimental animals were decapitated on day 5 without pain and continued with the stage of making microscopic preparations of tissue taken and fixed with buffer formalin 10% for a maximum of 24 hours.Results : The results showed that the average number of fibroblasts in the administration of extract pegagan gel was 15% with 400 cells, 10% was 291 cells, 5% was 262 cells and the average CMC Na gel group was 74 cells.Then continued with the One Way Anova test and the Least Significant Difference (LSD) test and results showed the average number of fibroblast cells in the four groups after being given treatment was significantly different with a significant level (ρ) < 0.05 and followed by a post hoc test, it is known that the gel extract pegagan 5%, 10%, and 15% can increase the number of fibroblast cells.Conclusion : Extract pegagan gel 15% more increased the number of fibroblast cells than extract pegangan gel10% and 5%.